Correction: Biotinidase deficiency: Genotype-biochemical phenotype association in Brazilian patients. - Taciane Borsatto; Fernanda Sperb-Ludwig; Samyra E Lima; Maria R S Carvalho; Pablo A S Fonseca; José S Camelo; Erlane M Ribeiro; Paula F V de Medeiros; Charles M Lourenço; Carolina F M de Souza; Raquel Boy; Têmis M Félix; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0177503.].